Tensile Test Of Fly Ash-Polypropylene Hybrid Composite Via Ansys Simulation - Intan Syaqirah, Mohd Zulkifli; Ehtisham, Ahmed; Malvin, .; Wong, Freddawati Rashiddy; Muhammad Izzat Nor, Ma'arof (INTI International University, 2020)
The utilization of power plant by various nations is the direct result from the need to satisfy the ever increasing demand for electricity. One of the major drawback for the use of power plant is the resulting fly-ash waste. The goal of this study was to investigate the tensile strength of a newly developed fly-ash-polypropylene (PP) hybrid composite via Finite Element Analysis (FEA) simulation. Four (4) types of hybrid composite were simulated in this study which were: (i) 100% PP, 0% fly-ash, (ii) 90% PP, 10% fly-ash, (iii) 80% PP, 20% fly-ash, and (iv) 70% PP, 30% fly-ash. The properties of the composite for four (4) different samples were obtained from the literature and via calculations. The results showed that shows that for sample 1, 2, 3 and 4; the maximum stress of 20.218 MPa, 20.171 MPa, 16.859 MPa and 15.37 MPa were simulated. Furthermore, only sample 1 managed to record the factor of safety to be above 1.0. Hence, it is safe to deduce that tensile strength of the newly developed fly-ash- polypropylene hybrid composite is decreasing with the increasing percentage of fly-ash. The reduction in tensile strength proves that there is the absent of a chemical bond between the polypropylene and fly-ash. Further addition of fly-ash onto the hybrid composite increases the material linear elastic fracture because of creation of lager defect. Therefore, the fly-ash-polypropylene hybrid composite is not suitable for the engineering application where tensile strength matters the most. For future studies, other types of mechanical properties assessment is recommended to be conducted on the fly-ash-recycled-plastic hybrid composite.